العوامل الاقتصادية والاجتماعية للهجرة غير الشرعية للسودانيين بدولة ليبيا (مدينة بنغازي انموذجاً) - محمد محمود, أسمهان عبدالله; عثمان, سعيد علي كوزي; بابكر, أمل مكي عبدالرحمن (Gezira Journal of Educational Sciences and Humanities, 2026)
هدفت الدراسة إلى التعرف على العوامل الاقتصادية التي ساهمت في الهجرة غير الشرعية للسودانيين بدولة ليبيا، مدينة بنغازي ، وكذلك الوقوف على العوامل الاجتماعية التي لها  دور في الهجرة غير الشرعية للسودانيين. أتبعت الدراسة المنهج  التاريخي والوصفي والتحليلي، ولتحقيق الأهداف اعتمدت الدراسة على البيانات الثانوية ، بالإضافة إلى الأولية التي جمعت عن طريق الملاحظات الميدانية المباشرة و والمقابلة الشخصية، الاستبانة، وتم أخذ عينة بلغ حجمها الكلي (100)  مهاجراً  بلغت (8%) من مجتمع الدراسة، ولتحليل البيانات تم استخدام برنامج الحزمة الإحصائية للعلوم الاجتماعية (SPSS). توصلت الدراسة إلى نتائج منها: أن 88.2% من المهاجرين السودانيين لا يرغبون بالإقامة في مدينة بنغازي بل يتخذونها منطقة عبور لأوروبا، يتعرض المهاجرون السودانيون غير الشرعيين لمخاطر عدة حيث أكد حوالي 52.9% تعرضهم  للابتزاز المادي والاتجار بالبشر والسرقة والنهب والقتل، حوالي 47.1% يتعرضون لمضايقات من قبل السلطات الليبية، وأن العوامل الاقتصادية هي المحرك الأساسي للهجرة غير الشرعية،  وهذا ما أكده 70.6% من المهاجرين ، يرى  52.9 % أن العوامل الاجتماعية تأثيرها محدود ، كما أكد   % 47.1 أن عدم الاستقرار السياسي والأمني من العوامل الأساسية التي دفعتهم للهجرة غير الشرعية. بناءً على ذلك تُوصي الدراسة ب: توفير فرص عمل مناسبة لامتصاص البطالة بين الشباب والحد من رغبتهم في الهجرة غير الشرعية، تحسين المستوى التعليمي والتدريب المهني لتأهيل الشباب لسوق العمل وتقليل الحاجة إلى  الهجرة غير الشرعية، تحقيق الاستقرار السياسي والأمني كعامل أساسي لوقف النزوح القسري والحد من الدوافع السياسية للهجرة غير الشرعية. The study aimed to examine the socio-economic factors contributing to Illegal immigration among Sudanese nationals in Benghazi City, Libya. The study followed the historical, descriptive, and analytical method. To achieve its objective, the study relied on secondary data as well as primary data collected through direct field observations and a questionnaire. A random sample of (100) migrants was selected, representing (8%) of the total study population. The data was analyzed using the statistical package of social sciences (SPSS). The most important findings of the study are as follows: (88.2%) of Sudanese migrants do not wish to stay in the city of Benghazi; instead, they treat it as a transit point to Europe. Undocumented Sudanese migrants face numerous risks; approximately (52.9%) confirm they are subjected to financial extortion, human trafficking, theft, looting, and killing. Additionally, about (47.1%) face harassment by the Libyan authorities. Economic factors are the primary driver of illegal migration, as confirmed by (70.6%) of migrants, while (52.9%) of them believe that social factors have only a limited impact. Furthermore, (47.1%) confirm that political and security instability are among the primary factors driving them toward illegal migration. In light of the above-mentioned findings, the study recommends the following:  Suitable job opportunities should be provided to absorb unemployment among youth and curb their desire for illegal migration. Educational standards and vocational training should be improved to qualify young people for the labor market and reduce the need for illegal migration. Political and security stability should be achieved as a fundamental factor in stopping forced displacement and limiting the political motives behind illegal migration.